Organic Waste to Energy: Resource Potential and Barriers to Uptake in Chile - Garrido-Lazo, R (Elsevier B.V., 2021)
Achieving net-zero greenhouse gas emissions by 2050 requires a step-change in resource management, and the utilisation of organic waste is currently an untapped opportunity in Latin America. This study carries out a quantitative and qualitative assessment of organic waste-to-energy potentials for the Chilean context. First, it produces a comprehensive quantification of organic waste, including annual crop residues, horticulture residues, livestock manure and OFMSW by region; then it estimates the energy potential of these bioresources; and finally, it conducts a series of stakeholder interviews determining barriers to greater waste-to-energy utilisation. The results show that the total bioenergy potential from waste is estimated at 78 PJ/yr (3.3% of annual energy demand), being livestock manure (41%) and annual crop residues (28%) the main sources, arising mostly from three regions. The stakeholder elicitation concluded that financial, technical, and institutional barriers prevent waste utilisation, highlighting the needs to address elevated investment costs and high reliance on landfilling practices, which together with public policies could enable the full exploitation of these resources to ensure energy security and resource efficiency. © 2021